(untitled) (Research, Society and Development, 2022)
Objective: To cover the importance of nurses working in Primary Health Care to carry out an effective home visit for the puerperal woman and newborn, in order to avoid complications and resolve doubts of the mother, and family in the puperal period. Methodology: This is a literature review study, which were searched from July to August 2022, articles indexed in LILACS, SciELO, Pubmed and Google Scholar databases. Results: The bibliographic survey provided the authors with a holistic look at the puerperal or postpartum period, which is defined as the period after birth, after the expulsion of the placenta, which extends up to 42 days of delivery. Therefore, home visits during this period are considered an essential tool that will contribute to the reduction of morbidity and mortality and to a better monitoring of the health of the Newborn and the puerperal woman. Conclusion: It is concluded that the home visit of the puerperal period must have a systematic and participatory planning of goals, strategies and actions that are recommended by the Ministry of Health, contributing to the reduction of morbidity and mortality for the puerperal woman and the newborn are essential to problematize and prepare team members for the performance of roles and attributions in the puerperium.